Російський досвід вирішення проблем ліквідності іпотечних облігацій та перспективи його застосування в україні - Зельцер, Є. Р. (Ways to Improve Construction Efficiency, 2013)
The mechanism of arising mortgage bond liquidity of Russian federal «Agency for Housing Mortgage Lending» has been analyzed in the article. The possibility of using of the Russian experience in Ukraine has been studied.